Revealing the Intrinsic Atomic Structure and Chemistry of Amorphous LiO2-Containing Products in Li-O2 Batteries Using Cryogenic Electron Microscopy - Zhang, Peng; Han, Bing; Yang, Xuming; Zou, Yucheng; Lu, Xinzhen; Liu, Xiao; Zhu, Yuanmin; Wu, Duojie; Shen, Shaocheng; Li, Lei; Zhao, Yong; Francisco, Joseph S; et al. (Journal of the American Chemical Society, 2022)
Aprotic lithium-oxygen batteries (LOBs) are promising energy storage systems characterized by ultrahigh theoretical energy density. Extensive research has been devoted to this battery technology, yet the detailed operational mechanisms involved, particularly unambiguous identification of various discharge products and their specific distributions, are still unknown or are subjects of controversy. This is partly because of the intrinsic complexity of the battery chemistry but also because of the lack of atomic-level insight into the oxygen electrodes acquired via reliable techniques. In the current study, it is demonstrated that electron beam irradiation could induce crystallization of amorphous discharge products. Cryogenic conditions and a low beam dosage have to be used for reliable transmission electron microscopy (TEM) characterization. High-resolution cryo-TEM and electron energy loss spectroscopy (EELS) analysis of toroidal discharge particles unambiguously identified the discharge products as a dominating amorphous LiO2 phase with only a small amount of nanocrystalline Li2O2 islands dispersed in it. In addition, uniform mixing of carbon-containing byproducts is identified in the discharge particles with cryo-EELS, which leads to a slightly higher charging potential. The discharge products can be reversibly cycled, with no visible residue after full recharge. We believe that the amorphous superoxide dominating discharge particles can lead researchers to reconsider the chemistry of LOBs and pay special attention to exclude beam-induced artifacts in traditional TEM characterizations.Aprotic lithium-oxygen batteries (LOBs) are promising energy storage systems characterized by ultrahigh theoretical energy density. Extensive research has been devoted to this battery technology, yet the detailed operational mechanisms involved, particularly unambiguous identification of various discharge products and their specific distributions, are still unknown or are subjects of controversy. This is partly because of the intrinsic complexity of the battery chemistry but also because of the lack of atomic-level insight into the oxygen electrodes acquired via reliable techniques. In the current study, it is demonstrated that electron beam irradiation could induce crystallization of amorphous discharge products. Cryogenic conditions and a low beam dosage have to be used for reliable transmission electron microscopy (TEM) characterization. High-resolution cryo-TEM and electron energy loss spectroscopy (EELS) analysis of toroidal discharge particles unambiguously identified the discharge products as a dominating amorphous LiO2 phase with only a small amount of nanocrystalline Li2O2 islands dispersed in it. In addition, uniform mixing of carbon-containing byproducts is identified in the discharge particles with cryo-EELS, which leads to a slightly higher charging potential. The discharge products can be reversibly cycled, with no visible residue after full recharge. We believe that the amorphous superoxide dominating discharge particles can lead researchers to reconsider the chemistry of LOBs and pay special attention to exclude beam-induced artifacts in traditional TEM characterizations.